The Effects of Bevacizumab in Augmenting Trabeculectomy for Glaucoma: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 15 (April 2016) - Liu, Xiaoyan; Du, Liang; Li, Ni
Abstract : Abstract: The aim of the study was to assess the effects of bevacizumab in augmenting trabeculectomy for glaucoma. We searched the databases of Cochrane Library, PubMed, Embase, CNKI, and VIP. All the databases were retrieved from the time databases established to September, 2015. The keywords we used were as follows: "bevacizumab, " "anti-VEGF, " "avastin, " "trabeculectomy, " "glaucoma, " and so on. We used a method of the freedom word search and the MeSH search combined, which was recommended by Cochrane Systematic Review Manual 5.1.2. Randomized controlled trails (RCTs) of frequently used bevacizumab in trabeculectomy for glaucoma were included. Study selection, data extraction, quality assessment, and data analysis were performed according to the Cochrane standards. Eight randomized controlled trails involving 212 eyes in the experimental (bevacizumab or bevacizumab + mitomycin C) groups and 214 eyes in the control (mitomycin C or placebo) groups were selected. Compared with placebo, bevacizumab significantly increased the complete success rate [OR = 2.79, 95%CI, (1.47, 5.29), P  = 0.002], what else, bevacizumab also significantly decreased the intraocular pressure (IOP) [MD = 3.07, 95% CI, (0.87, 5.27), P  = 0.006] at the 6-month after trabeculectomy and the number of antiglaucoma medications [MD = 1.23, 95% CI, (0.66, 1.80), P   <  0.0001]. Additionally, it also increased the risk of bleb leak [OR = 5.24, 95% CI, (1.30, 21.10), P  = 0.02]. When compared with mitomycin C (MMC), bevacizumab significantly increased the rate of encysted blebs [OR = 4.62, 95% CI, (1.02, 20.91), P  = 0.05]. However, there was no significantly difference between the bevacizumab + MMC groups and MMC groups whatever the items were. Bevacizumab was an effective way in trabeculectomy concerning the complete success rate, IOP, and anti-glaucoma medications reduction when compared with placebo; however, it increased the risk of bleb leakage. And it significantly increased the rate of encysted blebs compared with MMC.